Development of a micromechanical damage model for assessing lifetime due to cyclical mechanical loading. Issue 10 (11th July 2013) - Krätschmer, D.; Roos, E.
ABSTRACT: The safe assessment of temporary service load changes necessitates a fatigue analysis in general. Recent computation methods try to include the microcrack growth corresponding to fatigue in the assessment of the material damage. A new damage model, which is based on the development and evolution of microcracks, has been developed. The stochastic character of the initiation and growth of microcracks enables a more realistic description of the material damage. Within this scope the development of the model is presented and its correlation with experimental results is shown. Fatigue tests under uniaxial and torsional loadings were carried out with specimens made of austenitic stainless steel X6CrNiNffe1666‐bib‐0018–10 S (1.4550). The calculated results of the microcrack length distribution show for both uniaxial and multiaxial loading a good agreement with experimentally achieved data. Using the expectation value of the calculated surface microcrack distribution as the governing variable to predict the number of cycles to crack initiation NA, a good correlation between lifetime and local microcrack length distributions for complex loading conditions can be drawn.